Review of threatened Malagasy freshwater fishes in zoos and aquaria: The necessity of an ex situ conservation network—A call for action. Issue 3 (6th December 2021) - Leiss, Laura; Rauhaus, Anna; Rakotoarison, Andolalao; Fusari, Charles; Vences, Miguel; Ziegler, Thomas
Abstract: Madagascar's biota is characterized by an extraordinary species richness, with a high degree of endemism. The island's freshwater habitats harbor numerous micro‐endemic species, restricted to particular regions and thus particularly at risk of extinction, due to deforestation, overfishing, and introduction of exotic species. The present study investigates for which threatened Malagasy freshwater fish species ex situ populations have already been established, as a baseline to prioritize actions to develop an effective ex situ conservation breeding network. Populations in zoos and aquaria were primarily determined using the Zoological Information System. Of 173 fish species recorded from Malagasy freshwater habitats, 123 exclusively inhabit freshwater; 79 of these are endemic to Madagascar, and 50 are classified as threatened. Our survey found 21 Malagasy freshwater fish species kept in zoos worldwide, of which 19 are endemic and threatened (22 if counting species kept by private breeders). Nine of the 19 Malagasy freshwater fish species kept in zoos have successfully reproduced within the 12 months preceding our survey. The ex situ conservation activities for threatened Malagasy freshwater fishes thus have not improved significantly since the strong start in the early 2000s. More than half of the 50 threatened endemic Malagasy freshwater fish species (viz. 31 species) are not kept ex situ, including 11 species ranked as Critically Endangered. Based on these findings we call for a better distribution of offspring among institutions, including private breeders in the framework of citizen conservation initiatives; a closer connection of ichthyological field research in Madagascar with conservation breeding efforts to set up ex situ populations—both in Madagascar and abroad—of species not yet kept in captivity; and the development of effective, integrated in situ and ex situ conservation strategies. Graphical abstract: Total number of Malagasy freshwater fishes ( n  = 4267) globally held in zoos (bars coloured according to family; * = endemic species; NT = nonthreatened species), after Zoological Information System (ZIMS). RESEARCH HIGHLIGHTS: Of the 79 endemic Malagasy freshwater fish species 50 are ranked as threatened and only 19 kept in zoos worldwide. We propose an ex situ conservation breeding network for threatened Malagasy freshwater fish species linked with in situ strategies.